2016
DOI: 10.21767/2471-8165.1000031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sperm DNA Fragmentation and Aneuploidy in 109 Infertile Patients: Are the Two Parameters Correlated?

Abstract: Purpose: To evaluate the association between sperm DNA integrity and chromosomes aneuploidies in a considerable population of infertile patients undergoing assisted reproductive treatment (109 male) characterized by both normal and abnormal semen parameters. Methods:In 109 infertile patients with normal and abnormal semen parameters, the assessments of sperm DNA fragmentation by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling (TUNEL) and chromosome aneuploidy by fluorescence in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…These results are consistent with other studies from Peru, such as those of Acosta & Dueñas (2014), which found a mean DFI value among ALTERED patients to be significantly higher than in the NORMO patients (22.95 ± 12.25 vs 14.39 ± 9.06); and Acosta et al (2016) found significant differences in the mean value of DFI between ALTERED and NORMO patients (21.51 ± 14.18 vs 14.08 ± 7.08, respectively). Similar results were reported by other studies evaluating fertile and infertile patients using the SCD test (Fernández et al, 2005;Chohan et al, 2006;Evgeni et al, 2015;Wiweko & Utami, 2017;Majzoub et al, 2019) and other tests (Sergerie et al, 2005;Chohan et al, 2006;Sheikh et al, 2008;Mayorga-Torres et al, 2013;Di Santo et al, 2016). On the other hand, the study by Khalili et al (2006) did not find significant differences in the value of DFI between fertile and infertile patients using the acridine orange staining test.…”
Section: Discussionsupporting
confidence: 86%
“…These results are consistent with other studies from Peru, such as those of Acosta & Dueñas (2014), which found a mean DFI value among ALTERED patients to be significantly higher than in the NORMO patients (22.95 ± 12.25 vs 14.39 ± 9.06); and Acosta et al (2016) found significant differences in the mean value of DFI between ALTERED and NORMO patients (21.51 ± 14.18 vs 14.08 ± 7.08, respectively). Similar results were reported by other studies evaluating fertile and infertile patients using the SCD test (Fernández et al, 2005;Chohan et al, 2006;Evgeni et al, 2015;Wiweko & Utami, 2017;Majzoub et al, 2019) and other tests (Sergerie et al, 2005;Chohan et al, 2006;Sheikh et al, 2008;Mayorga-Torres et al, 2013;Di Santo et al, 2016). On the other hand, the study by Khalili et al (2006) did not find significant differences in the value of DFI between fertile and infertile patients using the acridine orange staining test.…”
Section: Discussionsupporting
confidence: 86%